Motivasi Anggota Kelompok Tani dalam Membudidayakan Tanaman Cabai (Kasus pada Kelompok Tani Catur Amerta Sari, Banjar Pura, Desa Sebudi, Kecamatan Selat, Kabupaten Karangasem) - WIDIARTHA, I GEDE WAHYU; PUTRA, I GEDE SETIAWAN ADI; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017, 2017)
Motivation of Farmers’ Group Members in Chili Plant Growing (The Case of Farmers’ Group of Catur Amerta Sari, Banjar Pura, the Village of Sebudi, Sub-District of Selat, Karangasem Regency) Cultivation of chili plants is conducted by members of the Farmers’ Group of Catur Amerta Sari, Banjar Pura, the village of Sebudi, certainly based on the high intrinsic and extrinsic motivation of the members of farmers’ group. Under these conditions, the purpose of the study was to determine the level of intrinsic and extrinsic motivation of the farmers’ group members of Catur Amerta Sari in Banjar Pura, the village of Sebudi in cultivating chili, and to find out the more influential motivation in influencing the members of Farmers’ Group of Catur Amerta Sari in the cultivation of chilies. The data in this study were obtained through interviews and observation methods, which were then analyzed using qualitative descriptive methods. The research results showed that the intrinsic motivation is classified into higher category with achieving an average score of 4.17 and the extrinsic motivation is classified into high category with achieving an average score of 4.00. The more dominant influential motivation was the intrinsic motivation. This is due to most of the Catur Amerta Sari’s Farmers still cultivate chili plants in order to meet the needs of its physiology. The agricultural extension agents must coordinate the pest and disease control that still often attack the chili plants. The government is expected to provide support of agricultural production facilities and new innovations that can reduce the problems faced by the members of farmer groups.